Metamorphism of retroeclogites from the Passos Nappe, Southern Brasília Orogen - Santos, Caio A.; Luvizotto, George L. [UNESP]; Moraes, Renato; Fumes, Regiane A. [UNESP]; Zack, Thomas (Elsevier, 2021)
High-pressure metamafic rocks from the Passos Nappe, Southern Brasília Orogen, have been traditionally interpreted as highly retrogressed eclogites, even though no reliable P-T conditions were available thus far. In this work, samples from the least retrogressed sample were studied using petrography, mineral and whole-rock chemical analysis, thermodynamic modelling, and rutile U–Pb geochronology, with the objective of unravelling its metamorphic history. The studied rocks are, descriptively, hornblende-garnet-clinopyroxene schists. Garnet and hornblende occur in a matrix composed of clinopyroxene-plagioclase symplectite, with garnet being surrounded by plagioclase-hornblende coronas. A combination of thermodynamic modelling, Zr-in-rutile and Ti-in-quartz thermobarometry suggests peak temperature to be 725 ± 30 °C, attained at a minimum pressure of ≈16 kbar, and data from rutile and quartz crystals included in garnet qualitatively indicate an earlier stage at higher P and lower T, constraining a clockwise P-T path. No evidences of UHP metamorphism were found thus far. A lower intercept age of 579 ± 23 Ma was calculated from rutile data, which is identical, within uncertainty, to rutile ages obtained previously in units immediately above the rocks studied here. The data suggests that these rocks were submitted to a different P-T path compared to the adjacent units, and that they were subducted to depths of at least ≈60 km and tectonically emplaced amid the surrounding metapelitic rocks before 579 Ma, which is compatible with current models for the evolution of the Southern Brasilia Orogen.
Keywords: Pseudosection; Retroeclogite; Southern Brasília Orogen; Trace-element thermobarometry